Analisis Faktor yang Mempengaruhi Penggunaan Instrumen Derivatif Valuta Asing sebagai Pengambilan Keputusan Hedging (Studi pada Perusahaan Manufaktur Sub Sektor Automotive and Allied Products yang terdaftar di BEI Periode 2011-2017) - Ivonne Bonita (Universitas Kristen Maranatha, 2019)
This paper aims to examine the effect of the variable debt equity ratio (DER), financial distress, growth opportunity, liquidity and firm size on the use of derivative instruments as a means of taking hedging decisions. The population and sample of the company are classified as automotive and allied products sub sector manufacturing companies with annual data obtained from the Indonesia Stock Exchange in the period 2011 to 2017, based on the Indonesia Capital Market Directory 2015. To obtain valid research results, the sampling technique used in the study is a purposive sampling method. Hypothesis testing uses a logistic regression model. Keywords: Hedging, DER, Financial Distress, Firm Size, Logistic Regression